2015
DOI: 10.1038/bjc.2015.300
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression signature of castration-resistant prostate cancer: the microRNA-221/222 cluster functions as a tumour suppressor and disease progression marker

Abstract: Background:Our present study of the microRNA (miRNA) expression signature in castration-resistant prostate cancer (CRPC) revealed that the clustered miRNAs microRNA-221 (miR-221) and microRNA-222 (miR-222) are significantly downregulated in cancer tissues. The aim of this study was to investigate the functional roles of miR-221 and miR-222 in prostate cancer (PCa) cells.Methods:A CRPC miRNA signature was constructed by PCR-based array methods. Functional studies of differentially expressed miRNAs were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
136
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 37 publications
6
136
0
Order By: Relevance
“…Several miRNAs (miR-21, miR-31, miR-34 and miR-124) can regulate the androgen receptor expression, and simultaneously, AR can regulate the expression of several miRNAs (miR-21, miR-27a, miR-34, miR-125b, miR-221 and let-7) [65]. Goto et al [66] recently demonstrated that miR-221 and 222 were significantly downregulated in CRPC specimens, even when this cluster was previously described to be upregulated ( Figure 3) [67,68]. This fact shows the dynamic status of miRNAs in the development of PCa, regulating the same miRNA different targets depending on the point of the cancer progression.…”
Section: Role Of Mirnas In Prostate Cancermentioning
confidence: 99%
“…Several miRNAs (miR-21, miR-31, miR-34 and miR-124) can regulate the androgen receptor expression, and simultaneously, AR can regulate the expression of several miRNAs (miR-21, miR-27a, miR-34, miR-125b, miR-221 and let-7) [65]. Goto et al [66] recently demonstrated that miR-221 and 222 were significantly downregulated in CRPC specimens, even when this cluster was previously described to be upregulated ( Figure 3) [67,68]. This fact shows the dynamic status of miRNAs in the development of PCa, regulating the same miRNA different targets depending on the point of the cancer progression.…”
Section: Role Of Mirnas In Prostate Cancermentioning
confidence: 99%
“…Interestingly, genes targeted by these miRNA passenger strands (SPOCK1, MELK, NCAPG, BUB1, and CDK1) were overexpressed in naive PCa and CRPC specimens and high expression of these genes predicted poor survival in patients with PCa [18]. Analyses of our signatures revealed that miR-205-5p was significantly downregulated in naive PCa and CRPC specimens [16,17]. Our previous study showed that restoration of miR-205-5p inhibited cancer cell aggressiveness through its targeting of centromere protein F (CENPF).…”
Section: Discussionmentioning
confidence: 88%
“…Based on this strategy, we have addressed antitumor miRNAs and associated cancer pathways in naive PCa and CRPC cells [16,17]. For example, miR-26a, miR-26b, miR-218, the miR-29-family, and miR-223 were downregulated in naive PCa tissues and these miRNAs inhibited cancer cell migration and invasion through targeting of genes involved in the extracellular matrix [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations